2014
DOI: 10.1212/wnl.0000000000000359
|View full text |Cite
|
Sign up to set email alerts
|

EEG-fMRI in myoclonic astatic epilepsy (Doose syndrome)

Abstract: In addition to the thalamocortical network, which is commonly found in idiopathic generalized epilepsies, GSW in patients with MAE are characterized by BOLD signal changes in brain structures associated with motor function. The results are in line with animal studies demonstrating that somatosensory cortex, putamen, and cerebellum are involved in the generation of myoclonic seizures. The involvement of these structures might predispose to the typical seizure semiology of myoclonic jerks observed in MAE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
8
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 35 publications
3
8
1
Order By: Relevance
“…Intriguingly, the cortical networks observed in GLUT1DS patients are very similar to the one described, by means of EEG-fMRI, in patients with ‘Doose syndrome’ or Myoclonic Astatic Epilepsy (MAE) (Moeller et al, 2014). This commonality is of particular interest since MAE has been reported as one of the possible phenotypes of GLUT1DS (Mullen et al, 2011).…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…Intriguingly, the cortical networks observed in GLUT1DS patients are very similar to the one described, by means of EEG-fMRI, in patients with ‘Doose syndrome’ or Myoclonic Astatic Epilepsy (MAE) (Moeller et al, 2014). This commonality is of particular interest since MAE has been reported as one of the possible phenotypes of GLUT1DS (Mullen et al, 2011).…”
Section: Discussionsupporting
confidence: 65%
“…This commonality is of particular interest since MAE has been reported as one of the possible phenotypes of GLUT1DS (Mullen et al, 2011). With respect to the BOLD findings previously reported in MAE (Moeller et al, 2014), and more in general to GGE sub-syndromes, our GLUT1 population didn't show any increase in BOLD signal at thalamic level and no decreases in the Default Mode Network (DMN) at a group level. By contrast, GLUT1DS revealed bilateral activation in the putamen and different premotor and parietal areas (Fig.…”
Section: Discussionsupporting
confidence: 58%
“…Several studies in Lennox–Gastaut syndrome (173175) have shown hemodynamic involvement of brainstem, thalamus, and basal ganglia during paroxysmal fast activity and slow spike-and-wave discharges, underlying the importance of cortical–subcortical networks in Lennox–Gastaut syndrome. A group-analysis study in patients with myoclonic-astatic-epilepsy (176) showed that GSWD are related not only to a thalamo-cortical network (commonly found in IGE), but also to brain areas associated with motor function, suggesting that the involvement of these structures may predispose to the typical myoclonic jerks observed in this syndrome.…”
Section: Evidence For Brain Network Involved In Epileptic Activitymentioning
confidence: 99%
“…A potential corroboration of EMAs belonging to the spectrum of epileptic encephalopathies may derive from the recent development of functional neuroimaging. In particular, an EEG‐fMRI study on patients with EMAs showed that the discharges associated with generalized spike‐waves (GSWs) were associated with evidence of metabolic changes in the thalamo‐cortical network, commonly found in generalized epilepsies, as well as brain structures associated with motor function, such as the putamen and the premotor cortex (Moeller et al ., ). Interestingly, the brainstem was also deactivated in relation to GSWs, presented by two of the 11 patients studied.…”
Section: Discussionmentioning
confidence: 97%